The Effects of Some Plant Nutrition Applications on the Bioactive Compounds of Grapevine (Vitis vinifera L.) - Elver AKCAN; Ethem Ömer BAS; Ruhan İlknur GAZIOGLU SENSOY (ISPEC Journal of Agricultural Sciences)
The basis of the study was formed by the application of Humic Acid (HA) and Rock Phosphate (RP), which are used in different doses as organic plant nutrition material, to the vineyard in early spring. As a plant material, the local variety Sepirze (Vitis vinifera L.), which is extensively produced in Mardin/Türkiye, is used for table consumption as well as being used for wine in small businesses. Analyzes were made to determine the effects of plant nutrition applications on acidity, pH, TSS and maturity index values, total phenolic content, and antioxidant activity in grape berries; The phenolic content and antioxidant activity were analyzed separately in the berry flesh, skin, and seed sections, and it was tried to determine which part of the fruit was more affected by the applications. When the physicochemical prosperities of the grains were evaluated, the TSS content was found to be significantly (P<0.01) varied among the applications. In addition, it was observed that plant nutrition applications had an increasing effect on the maturity index when compared to control vines without any application. Considering the different parts of the grape, phenolic and antioxidant amounts were found to be significantly (P<0.01) different. The highest phenolic and antioxidant ratios were determined in the seed, followed by skin and flesh. Plant nutrition applications increased the phenolic content in whole grape berries; Moreover, the antioxidant activity was found to be significantly varied among the applications.